Masalah Penyesuaian Diri pada Remaja dengan Hambatan Perkembangan Fisik dalam Kajian Literatur BK - Regita Nur'aini Yahya; Elya Anggun Wilujeng; Calista Ramadhani Ersani; Sarah Jelita Br. Sitanggang; Desita Lia Monika; Denok Setyawati; Muhammad Farid Ilhamuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Adolescence is a crucial period marked by various changes, including physical, emotional, and social development. For adolescents who experience physical impairments, the process of adaptation becomes more challenging, as they must cope not only with changes within themselves but also with increasingly complex environmental demands. This study aims to explore how adolescents with physical impairments experience difficulties in adaptation from the perspective of guidance and counseling. The method used is a literature review, examining various sources such as journals, books, and related research findings. The results of this study indicate that adolescents’ ability to adapt is strongly influenced by internal factors, such as self-acceptance and emotional regulation skills, as well as external factors, including support from family and peers. Adolescents with physical impairments often experience low self-confidence, difficulties in social interaction, and a tendency to withdraw from their social environment. However, these conditions are not permanent. With appropriate support and effective guidance and counseling services, these adolescents have a significant opportunity to grow and adapt in a positive way.